1984
DOI: 10.1002/cm.970040506
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule crossbridging by Chlamydomonas dynein

Abstract: Dynein, obtained from axonemes of Chlamydomonas, binds by both its A and B ends to microtubules assembled from twice cycled (2X) and purified (6S) brain tubulin as well as to microtubules in native spindles, thereby inducing microtubule crossbridging. The two ends of the dynein arm exhibit distinct binding characteristics for the different microtubule preparations. Greater than 99% of the dynein arms are bound exclusively by their B ends to microtubules assembled from 6S tubulin in the presence of dynein and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 43 publications
1
9
1
Order By: Relevance
“…A previous study showed by electron microscopy of microtubule cross-sections that up to about four rows of dynein arms become attached to a cytoplasmic microtubule upon addition of high-salt extracts from axonemes (containing OADs and ODADCs) (27). In contrast, in our experiments, the saturating amount of DC1-2-3 bound to microtubules was about two per 24 nm.…”
Section: Resultscontrasting
confidence: 83%
“…A previous study showed by electron microscopy of microtubule cross-sections that up to about four rows of dynein arms become attached to a cytoplasmic microtubule upon addition of high-salt extracts from axonemes (containing OADs and ODADCs) (27). In contrast, in our experiments, the saturating amount of DC1-2-3 bound to microtubules was about two per 24 nm.…”
Section: Resultscontrasting
confidence: 83%
“…This prompted us to focus on the complex of the axonemal dynein and the microtubules. As reported previously, flagellar outer-arm dynein molecules are aligned on a microtubule in a selforganizing manner with the interval of 24 nm (30,31). Furthermore, the dense cluster of dynein molecules on a microtubule enables the complex to travel a long distance along another microtubule (>10 μm) toward the minus end in the presence of ATP (32,33).…”
Section: Significancesupporting
confidence: 53%
“…We mixed the microtubule fragments with crude axonemal dynein extracted from Chlamydomonas. At this point, outer-arm dynein molecule should be associated with a microtubule at its ATP-dependent motor stalk head and/or at its ATP-independent stem (31). To dissociate the ATP-dependent binding, we added ATP to the mixture of dynein and microtubules.…”
Section: Significancementioning
confidence: 99%
“…However, since dynein can induce the transport of nonspecific particles such as latex beads , true reconstitution of organelle movement may be very difficult to assess. In more recent ex periments, it has been fo und that both inward and outward granule movement in fi sh melanophores can be blocked by exposure to UV light in the presence of vanadate, and that both directions of movement can be restored by ex ogenous brain dynein (114). Whether this indicates that dynein is involved in bidirectional transport, or, rather that photocleaved dynein acts to inhibit anterograde movement, remains unresolved.…”
Section: Role Of Dynein In the Cellmentioning
confidence: 97%